Dechema chemistry data series : vapor liquid equilibrium data collection 6b - Gmehling, J.; Onken, U.; Arlt, W (Frankfurt Dechema, 1997)
part 6b. Aliphatic hydrocarbons, Cb7(B-Cb18s
part 6b. Aliphatic hydrocarbons, Cb7(B-Cb18s
Keywords: Vapor-liquid equilibrium -- Tables